Pseudo cholinesterase-diagnostic and prognostic value in organophosphorus poisoning - J., Lokesh A.; G, Deepak U.; B., Venkatesh K.; K., Yuvaraj M. (International Journal of Research in Medical Sciences, 2017)
Background: Organophosphorus compound poisoning is a common clinical situation encountered in emergency department. The estimation of pseudo cholinesterase levels in plasma help to identify OP poisoning. Aim of this study was the levels of pseudo cholinesterase in plasma as a diagnostic aid in patients with suspected organophosphorus poisoning and to predict the prognosis and mortality based on pseudo cholinesterase activity. Methods: 390 cases of suspected organophosphorus compound poisoning were selected above 18 years of age. Detailed history and clinical examination were done. The serum levels of enzyme pseudo cholinesterase were estimated on 1st and 3rd and 6th day. Results: 61% were males, 39% were females. Age range 18-55 years. Most of the patients were admitted within 4 hours of consumption. 50% cases were mild, 26% were moderate and 24% were severe cases, Commonest clinical features were vomiting, diarrhea and abdominal cramps. Common signs were miosis (46%), difficulty in breathing (42%), cold calmmy skin, bradycardia. Patients who survived had raising values of enzyme levels and in patients who expired did not show much increase in enzyme values. Conclusions: In initial stages of poisoning, determining pseudo cholinesterase activity forms a reliable test. In patients who survived had values above 4300 U/L and showed increasing levels on successive days indicating better prognosis. Low values of enzymes in initial stages of poisoning as well as decreasing values on the third day indicate increased mortality.